Silent Persuasion and Empowerment of Republican Motherhood in Freeman’s The Revolt of ’Mother’ - Silwal, Deepa (The Mega Journal, 2025)
Mary E. Wilkins Freeman’s ‘The Revolt of ‘Mother’ presents a compelling portrayal of Republican Motherhood through the character of Sarah Penn, whose quiet resistance within the domestic sphere powerfully challenges patriarchal authority and unjust social norms. Drawing upon the notion of revolutionary spirit within Republican Motherhood, this paper explores how Sarah Penn, the female protagonist in Mary E. Wilkins Freeman’s “The Revolt of ‘Mother’", uses the silent persuasion of Republican motherhood to legitimize female rebellion, reveal her political agency, and redefine traditional female roles. Referring to resistance, this paper examines how this resistance comes to Sarah Penn, what leads her to become a revolting mother, and how she gains a new insight to fight for her rights. In doing so, this paper, scrutinizing the representation of rhetoric of justice, right, and democracy intermingled within the text, provides a new insight to look at the female’s position in family and society who can persistently contribute to social change.